Elaboration of food bar of kiwicha, pollen and honey - Quevedo Rojas, Tito Daniel (2022)
The objective of the present work was to elaborate a food bar of kiwicha, pollen and bee honey and to carry out the physicochemical, organoleptic and microbiological analyzes of the obtained product. The raw materials for the 3 treatments were weighed, the kiwicha was subjected to a thermal temperature of 120ºC / 20 sec, the mass was homogenized manually, placed on a rectangular plate, previously covered with aluminum foil, and placed in a rotary oven at a temperature constant 160 ° C / 15 min, the product was cooled to room temperature 24 ° C, removed from the mold and cut into 30-gram bars, packed in polypropylene film and heat-sealed. The research had three treatments depending on the honey: T1 = 15%, T2 = 20% and T3 = 25%. The treatments were evaluated by a semi-trained panel, which were subjected to an analysis of variance with 95% reliability using the Tuckey contrast test, determining that T2 as the best in terms of taste, consistency, smell and appearance. The nutritional composition of the best treatment based on 100 gr, resulted in: carbohydrates 65.38, proteins 1.97 and fats 3.10 in terms of micronutrients in mg: calcium 32.00, phosphorus 54.29, iron 5.61 and potassium 92.29. as well as: humidity of 15.65gr, acidity 0.078%, 94 ° B and pH: 6.50. The microbiological results indicated that the product meets the requirements “of the regulation on surveillance and sanitary control of food and beverages according to Decree No. 007-98-S. MINSA.